The Development of Green Technology Model in the Process of Making Gamelan, Klungkung Regency, Bali - I Ketut Gde Juli Suarbawa (Logic : Jurnal Rancang Bangun dan Teknologi, 2020)
The work bent on the smelting process which is very low and with the flame still open so that the heat from combustion is wasted into the environment has the potential to pollute the environment and expose the craftsmen to cause an increase in workload, subjective disorders and a decrease in work productivity. For this reason, one short case study was conducted with a pre and pos test group design that was carried out observationally on craftsmen in the bronze smelting process for gamelan raw materials. The workload was predicted by calculating the working pulse, fatigue and complaints of skeletal muscle craftsmen recorded by questionnaire. The results of the research data were analyzed descriptively to obtain a new design of the bronze metal smelting furnace model so that the work attitude was more ergonomic. The results showed that the work pulse increased to 132.42 ± 4.41 per minute or increased by 58.21 beats per minute, including in the category of "heavy" workload. The mean score of musculoskeletal disorders after work increased to 49.30 ± 4.98 and the mean score of fatigue complaints after work also increased to 50.12 ± 1.23. Work productivity decreased from 101.21 ± 5.21 at the beginning of work to be 95.42 ± 2.12 at the end of work. For that, a bronze metal smelting furnace is redesigned, namely redesigning the height of the work field to 60-65 cm from the floor so that the worker's work posture becomes natural and the top of the smelting furnace is equipped with a canopy to remove dust and heat from the workplace.